Cardiology training in South Africa – On the brink? - Doubell, Anton (SA Heart Journal, 2017)
More often than not, when we use the expression “on the brink”, we are referring to an impending bad situation. On the edge of a cliff without wings so to speak…, on the brink of disaster…, on the brink of ruin…, on the brink of collapse…, on the brink of extinction…. In the broad sense, “on the brink” refers to the point where a new or different situation is about to begin and it may not necessarily signal impending doom. On the contrary, it may refer to a sense of anticipation, of being primed, a state of readiness, champing at the bit. It may signal that it is all systems go.